2021
DOI: 10.5812/ijcm.115720
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection of Human Cytomegalovirus in Breast Cancer of Iranian Women Using Real-time PCR

Abstract: Background: The role of carcinogenic viruses in developing breast cancer has not yet been identified. Many studies have examined the association between breast cancer and human cytomegalovirus (HCMV), but conflicting results have been reported. Objectives: The aim of this study was to evaluate the levels of IgM & IgG antibodies against HCMV by identifying the viral genome in the breast tissue of women with breast cancer. Methods: A total of 60 patients with breast cancer and 60 healthy individuals (40 case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…In the MENA region six studies were found: three in Iran, two in Egypt, and one in Iraq. In these studies, CMV was detected in 6.3-54% of the BC tissue compared to 0-28% in controls [41][42][43][44][45]. In our study, CMV was detected in 13.6% of the patients, which aligns with previous studies [42][43][44]46].…”
Section: Discussionsupporting
confidence: 91%
“…In the MENA region six studies were found: three in Iran, two in Egypt, and one in Iraq. In these studies, CMV was detected in 6.3-54% of the BC tissue compared to 0-28% in controls [41][42][43][44][45]. In our study, CMV was detected in 13.6% of the patients, which aligns with previous studies [42][43][44]46].…”
Section: Discussionsupporting
confidence: 91%